2015
DOI: 10.1166/jbn.2015.2055
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Chemically Reduced Graphene Oxide for Targeted Photodynamic Therapy

Abstract: In this study, using chemically reduced graphene oxide (GO) as a model nanocarbon, we successfully developed a facile surface-functionalization strategy of nanocarbons to allow both biocompatibility and receptor targeted drug delivery. Polyvinylpyrrolidone (PVP) coating improves aqueous dispersibility and biocompatibility of GO, and provides anchoring sites for ACDCRGDCFCG peptide (RGD4C). Aromatic photosensitizer chlorin e6 (Ce6) can be effectively loaded into the rGO-PVP-RGD system via hydrophobic interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 38 publications
(38 reference statements)
1
35
1
Order By: Relevance
“…Interestingly, the fluorescence intensity of DVDMS in GO-PEG-DVDMS is dramatically enhanced. In comparison with our previous results, 3234 this phenomenon may be due to the intramolecular energy/ charge transfer of GO-PEG-DVDMS. 35 …”
Section: Resultssupporting
confidence: 55%
“…Interestingly, the fluorescence intensity of DVDMS in GO-PEG-DVDMS is dramatically enhanced. In comparison with our previous results, 3234 this phenomenon may be due to the intramolecular energy/ charge transfer of GO-PEG-DVDMS. 35 …”
Section: Resultssupporting
confidence: 55%
“…For instance, some dyes (Cy7 (44), Cy5 (45), IRDye800 (46), fluorescein (47), etc. ), nanoparticles (UCNPs (Tm 3+ /Er 3+ /Yb 3+ )) (48), and biomolecules (folic acid (17), RGD peptide (49), Herceptin (50), transferrin (51), hyaluronic acid (52), β-cyclodextrin (53), TRC105 (54), vascular endothelial growth factor (VEGF) (55), etc.) were covalently linked to GO/rGO for FL imaging and active targeting, respectively.…”
Section: Synthesis Of Graphene-based Nanomaterialsmentioning
confidence: 99%
“…Therefore, the surface functionalization of graphene and its derivatives is a crucial step for further biomedical applications. So far, two main strategies including covalent and non-covalent approaches, using various biocompatible coatings and targeting ligands, have been employed to engineer functionalized graphene-based materials with improved aqueous solubility, biocompatibility, and selectivity (49). For example, a variety of biocompatible and biodegradable macromolecules, such as polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), chitosan, and so on, have been used to modify graphene and its derivatives (26).…”
Section: Synthesis Of Graphene-based Nanomaterialsmentioning
confidence: 99%
“…Previous reports have demonstrated that addition of PVP can remarkably improve the biocompatibility of nanomaterials. 17,18 Tian et al 7 investigated the in vitro cytotoxicity of CuS superstructure modi¯ed by PVP, the results showed that no signi¯cant di®er-ences in the proliferation of the cells were observed in the absence or presence of 60-250 g/mL of CuS Table 1. O/C and Cu/C atomic ratio of GO, RGO-CuS from the XPS analysis.…”
Section: -5mentioning
confidence: 99%